Nature-based solutions with ecosystem services gains for managing saline waterlogged landscapes in semi-arid regions - Banyal, R.; Saini, Varun (Indian Farming, 2025)
Soil salinity and waterlogging are major land degradation challenges, particularly in arid and semi-arid regions, severely impacting agricultural productivity and ecological stability. In India, approximately 8.5 million hectares are affected, largely due to poorly managed irrigation systems lacking proper drainage. Bio-drainage, using deep-rooted trees to remove excess water through transpiration emerges as a sustainable, low-cost, and eco-friendly alternative to traditional drainage methods. Tree-based bio-remediation models, particularly those involving Eucalyptus tereticornis, Prosopis juliflora, Acacia nilotica, and Tamarix aphylla, have been successfully implemented across varying degrees of salinity and waterlogging. These models provide multiple ecosystem services: provisioning (fuelwood, timber, fodder), regulating (carbon sequestration, groundwater control, climate moderation), supporting (biodiversity enhancement, soil health), and cultural (aesthetic and recreational value). Eucalyptus-based models in moderately affected areas demonstrated the highest biomass yield, carbon sequestration, and microclimate regulation. Despite these benefits, cultural services and social values remain under-researched. For broader adoption, future strategies should emphasize ecosystem service valuation, community participation, and location-specific species selection to ensure long-term sustainability and resilience of saline waterlogged landscapes.